2008
DOI: 10.1080/17482960802031092
|View full text |Cite
|
Sign up to set email alerts
|

Are statin medications safe in patients with ALS?

Abstract: Statin medications for elevated cholesterol are one of the most commonly prescribed medications worldwide. The aim of this study was to determine if statin medications affect the rate of disease progression, the severity and frequency of muscle cramping, and serum CK levels in patients with ALS. We conducted a prospective cohort study in patients diagnosed with ALS with statin medication as the predetermined exposure variable and the rate of decline of the ALS Functional Rating Scale-Revised (ALSFRS-R) as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 22 publications
1
42
0
1
Order By: Relevance
“…Since then, the association between statins and ALS has become controversial. A recent study reported a strong association between statin medications and more rapid ALS progression, although the study was performed in only a small number of patients with the disease [9]. In contrast, a retrospective investigation of a large number of patients with ALS did not find any influence of statins on survival, concluding that statin treatments are safe for patients with ALS [10].…”
Section: Introductionmentioning
confidence: 96%
“…Since then, the association between statins and ALS has become controversial. A recent study reported a strong association between statin medications and more rapid ALS progression, although the study was performed in only a small number of patients with the disease [9]. In contrast, a retrospective investigation of a large number of patients with ALS did not find any influence of statins on survival, concluding that statin treatments are safe for patients with ALS [10].…”
Section: Introductionmentioning
confidence: 96%
“…A recent study [3] reported a strong association between statin medications and a more rapid rate of functional decline in small numbers of patients with ALS, leading those authors to advise exercising caution and discussing discontinuation or replacement of statin medications. In contrast, a large study whose information was retrieved from the database of several completed clinical trials found no indication of any impact of statins on the ALS disease course [4].…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia is associated to prolonged survival, and lipid-lowering drugs should be discontinued. 33,34 Statins have also been related to potential worsening of symptoms in myasthenia gravis. 23 In recent years, genetic factors have been increasingly thought to influence individual risk of statin-related myotoxicity.…”
Section: Individual Factorsmentioning
confidence: 99%